Influence of Strategic Planning on Banking Performance via Differentiation Strategy - Waisapi, Jeffry Yuliyanto (PT. Anagata Sembagi Education, 2024)
Effective strategic planning plays a crucial role in enhancing the performance of banking businesses. This research aims to analyze the impact of strategic planning on banking business performance through the implementation of differentiation strategy. Utilizing a quantitative approach, primary data was collected through surveys distributed to senior managers from several banks operating in various markets. Multiple linear regression analysis was employed to evaluate the relationship between strategic planning, strategic differentiation, and business performance. The research findings indicate that strategic planning significantly influences strategic differentiation in the context of the banking industry. Additionally, strategic differentiation also positively contributes to banking business performance. The implications of these findings are that banks implementing effective strategic planning tend to adopt better differentiation strategies, thereby enhancing their performance in facing intense market competition. This study provides valuable contributions to understanding the relationship between strategic planning, strategic differentiation, and business performance in the banking context. The results offer guidance for banks to improve their strategic planning practices and implement effective differentiation strategies to strengthen their competitive position in the market. Future research could explore additional factors influencing this relationship and broaden the industry scope to validate these findings more comprehensively.